Building Cross-Cultural Competence. How to Create Wealth from Conflicting Values - Hampden-Turner Ch. M. Charles (Chichester, John Wiley & Sons, 2004)
All Rights Reserved. No part of this publication may be reproduced stored in a retrieval system or transmitted in any form or by any means, electronic, mechanical, photocopying, recording, scanning or otherwise, except under the terms of the Copyright. Designs and Patents Act 1988 or under the terms of a licence issued by the Copyright Licensing Agency Ltd 90 Tottenham Court Road, London WIT 4LP. UK. without the permission in writing of the Publisher, with the exception of any material supplied specifically for the purpose of being entered and executed on a computer system, for exclusive use by the purchaser of the publication. Neither the authors) nor John Wiley & Sons, Ltd accept any responsibility or liability for loss or damage occasioned to any person or property through using the material, instructions, methods or ideas contained herein, or acting or refraining from acting as a result of such use. The author(s) and Publisher expressly disclaim all implied warranties, including merchantability of fitness for any particular purpose.